The impact of information infrastructure on agricultural industrial structure upgrading—a quasi-natural experiment based on the “broadband China” strategy - Huang, Huichun; Qian, Cheng; Wang, Yajing (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe development of information infrastructure constitutes an important driver for promoting high-quality agricultural development.MethodsUsing panel data of 223 prefecture-level cities in China from 2010 to 2022, this paper employs the “Broadband China” pilot policy as a quasi-natural experiment and constructs a staggered DID model to examine the impact of information infrastructure on agricultural industrial structure upgrading.Results and discussionThe results indicate that information infrastructure significantly facilitates the upgrading of the agricultural industrial structure, and the findings remain robust across a series of robustness checks. Heterogeneity analysis reveals that the positive effects are more pronounced in regions with better traditional infrastructure, higher population density, central and eastern locations, and major grain-producing and marketing balance areas. Mechanism analysis suggests that information infrastructure alleviates the scarcity and mobility constraints of agricultural production factors, thereby promoting structural upgrading. Based on these findings, this study recommends continued investment in information infrastructure, acceleration of agricultural innovation, and enhancement of talent cultivation to advance agricultural industrial upgrading and build an agricultural powerhouse.